Sistem Pakar untuk Diagnosa Penyakit yang Disebabkan oleh Nyamuk Berbasis WEB - Sadly Syamsuddin; Ahyuna Ahyuna (Lembaga Penelitian dan Pengabdian pada Masyarakat (LPPM) STMIK Global Informatika MDP, 2014)
The rapid developments in medical science and drug discovery and healing methods give birth to an interdependence between doctors and patients. Problems will arise when doctors can not identify exactly according to the symptoms of the disease suffered by the patient, as well as patients who may be difficult to give a clear explanation of the symptoms they suffer to the doctor. Therefore we need an expert system capable of adopting human knowledge or physician to a computer that is designed to model the human ability or the doctor solve problems like an expert. This study design an expert system expert system which aims to diagnose diseases caused by mosquitoes. This expert system modeling tool system dirancangan with the Unified Modeling Language (UML), MySQL as database management system SQL and PHP as the programming language. Once the system can diimplemntasikan we perform system testing with the Black Box. The results of the system built is an expert system that is able to diagnose a disease caused by a mosquito with a good degree of accuracy and misunderstandings that exist in each form component under test is not found at all.